Data-driven arts and cultural organizations: opportunity or chimera?. Issue 9 (2nd September 2022) - Nuccio, Massimiliano; Bertacchini, Enrico
ABSTRACT: Digital transformation has deeply influenced how innovation can rise in the production, distribution and consumption of cultural products. Although data-driven innovation has been proved effective in creating value across many business functions, the pace of adoption of strong data ecosystems seems slower for Arts and Cultural Organizations (ACOs). The paper theoretically explores how data analytics can affect different areas of innovation in the core cultural sectors. By integrating marketing intelligence, arts management and policy literature with illustrative evidence from secondary sources, we discuss the potential impact of data analytics for enhancing ACOs innovation. First, digitalization and connectivity have increased opportunities for customer engagement and empowerment, shifting cultural consumption from a transaction to a relationship with cultural organizations. Second, data-driven metrics allow ACOs and policy makers to match more effectively patterns of consumption and eventually to create value from harvesting and processing information. Finally, although ACOs are encouraged to review their traditional business models through this new trajectory, significant conceptual and organizational barriers question the benefits of data analytics and slow down its adoption. The paper contributes to the academic and policy debate on the role of data-driven innovation in arts management and marketing strategies for cultural organizations.